Manganese oxide/functionalised carbon nanotubes nanocomposite as catalyst for oxygen reduction reaction in microbial fuel cell. (21st September 2015) - Liew, Kien Ben; Wan Daud, Wan Ramli; Ghasemi, Mostafa; Loh, Kee Shyuan; Ismail, Manal; Lim, Swee Su; Leong, Jun Xing
Abstract: Manganese oxide/functionalised carbon nanotubes (MnO2 /f-CNT) nanocomposite is believed to be a good catalyst for oxygen reduction reaction (ORR) in a neutral solution; especially in a microbial fuel cell. The unique interaction between MnO2 and f-CNT will enhance the electron transfer process and facilitate the ORR. MnO2 /f-CNT nanocomposite was fabricated by in-situ hydrothermal synthesis method. The MnO2 /f-CNT was characterised by the field emission scanning electron microscope (FESEM). Raman spectra has proved there is more carbon defect on the surface of CNT after functionalization. XRD pattern showed amorphous MnO2 crystal existed in MnO2 /f-CNT catalyst. This study further employed cyclic voltammetry (CV) techniques to investigate catalytic activity. Lastly, microbial fuel cell test showed that MnO2 /f-CNT displayed higher power density (520 mW m −2 ) compared to CNT (275 mW m −2 ) and f-CNT (440 mW m −2 ). Moreover, the coulombic efficiency (28.65%) and COD removal value (86.6%) of MFC with MnO2 /f-CNT catalyst was higher amongst the three catalysts tested. This study concluded that MnO2 /f-CNT can be a good catalyst in microbial fuel cell application. Highlights: Synthesizing manganese oxide/functionalised carbon nanotubes nanocomposite. Characterization of manganese oxide/functionalised carbon nanotubes nanocomposite. Applying as the cathode catalyst in microbial fuel cell.